2005
DOI: 10.1016/j.jhazmat.2005.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons degradation by composting in a soot-contaminated alkaline soil

Abstract: This study deals with the biodegradation of the polycyclic aromatic hydrocarbons (PAH)s present in a soil contaminated by soot waste, characterised by a total PAHs content in the 200 mg kg −1 range. A challenging characteristic of the waste soil treated was its high alkalinity, with a pH of about 12.8. The waste came from a soot-contaminated area located in the industrial zone of Porto Marghera, Venice (Italy). The biodegradation process employed was the composting of the waste with sewage sludge and yard wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Bioremediation of contaminated soils by composting has been extensively reported in scientific literature, and these methods have proven to be effective in petroleum hydrocarbons degradation (Van Gestel et al 2003;Antizar-Ladislao et al 2004;Moretto et al 2005;Joo et al 2007;Zhang et al 2011;Laos et al 2012;Chen et al 2015). However, drilling cuttings composting bioremediation reports are scarce in scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…Bioremediation of contaminated soils by composting has been extensively reported in scientific literature, and these methods have proven to be effective in petroleum hydrocarbons degradation (Van Gestel et al 2003;Antizar-Ladislao et al 2004;Moretto et al 2005;Joo et al 2007;Zhang et al 2011;Laos et al 2012;Chen et al 2015). However, drilling cuttings composting bioremediation reports are scarce in scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…Despite mixing all o f the compost bins prior to sampling and using the same sampling procedure on all o f the bins, the replicate samples often varied significantly from each other. Moretto et al (2005) reported a similar problem when composting PAH contaminated soil. Compost construction, although carefully planned, can be heterogeneous due to the number o f feedstocks used and unique variations in rate o f organic matter decomposition (Miller 1993).…”
Section: Dynamics Of Phcs and Extractable Organic Matter In Compostmentioning
confidence: 89%
“…Huang et al (2004) reported that EC values follow a trend similar to pH values. Moretto et al (2005) reported an initial large decrease followed by a stabilization o f the EC. As with the other physiochemical properties o f compost, the values presented in literature vary greatly due to differences in the feedstocks used.…”
Section: Dynamics O F Physical and Chemical Properties During Compostingmentioning
confidence: 98%
See 2 more Smart Citations